2019
DOI: 10.1530/ec-19-0011
|View full text |Cite
|
Sign up to set email alerts
|

Elevated free fatty acids affect bovine granulosa cell function: a molecular cue for compromised reproduction during negative energy balance

Abstract: High-yielding dairy cows postpartum face the challenge of negative energy balance leading to elevated free fatty acids levels in the serum and follicular fluid thus affecting the ovarian function. Here, we investigated effects of physiological concentrations of palmitic acid (PA), stearic acid (SA) and oleic acid (OA) on the viability, steroid production and gene expression in a bovine granulosa cell (GC) culture model. Treatment with individual and combined fatty acids increased the CD36 gene expression, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 58 publications
2
29
0
Order By: Relevance
“…Together, these results suggest that high levels of ALA or cis-9, trans-11 CLA in FF can adversely affect GC by reducing both E2 and P4 production, which in turn could result in compromised ovarian cyclicity and impaired fertility in lactating cows. This is also in line with our recent study, where we could show that increased concentrations of OA in the follicular fluid can actually impair the functionality of GC in situ, thus obviously suppressing ovulation (21).…”
Section: Ala and Cis-9 Trans-11 Cla Modulate Gc Steroidogenesissupporting
confidence: 93%
See 1 more Smart Citation
“…Together, these results suggest that high levels of ALA or cis-9, trans-11 CLA in FF can adversely affect GC by reducing both E2 and P4 production, which in turn could result in compromised ovarian cyclicity and impaired fertility in lactating cows. This is also in line with our recent study, where we could show that increased concentrations of OA in the follicular fluid can actually impair the functionality of GC in situ, thus obviously suppressing ovulation (21).…”
Section: Ala and Cis-9 Trans-11 Cla Modulate Gc Steroidogenesissupporting
confidence: 93%
“…Primary GC culture and bovine serum albumin (BSA)-FA conjugate preparations were done as described earlier (21). For testing the effects of actual follicular concentration of ALA (Sigma-Aldrich,L2376) and cis-9, trans-11CLA (Sigma-Aldrich,16413) the media were replaced every 48 h with supplemented α-MEM media containing different concentrations of ALA (20,40, and 80 µM) or cis-9, trans-11 CLA (15, 30, and 60 µM) as BSA conjugates or non-conjugated BSA as vehicle control (Sigma-Aldrich A7030).…”
Section: Primary Gc Culturementioning
confidence: 99%
“…For HIF1A knockdown, GCs were transfected with 50 nM of antisense LNA negative control gapmer (A*A*C*A*C*-G*T*C*T*A*T*A*C* G*C), and anti HIF1A gapmer (A*C*T*G*A*T*C*G*A*A*G*G*A*-A*C*G) using TransIT-X2 ® transfection reagent (Mirus Bio, USA) as per the manufacturer's recommendations in a 24 well culture dishes for 6 days (from day 2 to day 8 of the culture). As established before, all cultured cells were subjected to different analyses on day 8 [20][21][22][23] .…”
Section: Methodsmentioning
confidence: 99%
“…Hence, analyzing the role of HIF1 under normoxic and hypoxic environments in the presence of FSH and IGF1 would offer important cues regarding GC physiology. Accordingly, the present investigation was carried out to identify HIF1 dependent transcriptional activity both under normoxic and hypoxic conditions using our renowned estrogen active culture model of bovine primary GC [20][21][22][23] .…”
mentioning
confidence: 99%
“…Valckx et al 2014 [29] showed that in vitro exposure of murine ovarian follicles to elevated levels of NEFAs resulted in the impairment of ovarian steroidogenesis and oocyte competence for fertilization. To further understand the physiological responses under in situ conditions, Sharma et al 2019 [30] took advantage of the ultrasound-guided injection approach to inject NEFAs (oleic acid; C18:1) into the dominant follicles of heifers in situ. Interestingly, the NEFA injected animals showed reduced ovulation rates and reduced production of E2 hormone compared to that of the control group of animals ( Fig.…”
Section: Fatty Acidsmentioning
confidence: 99%